Contribuição da variabilidade da frequência cardíaca na predição de eventos pós extração dentária - Chandretti, Leandro Alexandre (2014)
INTRODUCTION: Humans are formed by the union of systems. Because they are complex, these systems are dynamic and deterministic, with nonlinear behavior. The Heart Rate Variability (HRV) has been considered a good marker of homeostasis of the human organism. It is a noninvasive diagnostic method, often used in the assessment of autonomic control of the heart. Recent studies have shown that by HRV analysis, evaluating it in the time, frequency and Chaos, human bodies, in general, behave as complex nonlinear systems, predictable and ordered reactions, however apparently random OBJECTIVE: To evaluate the contribution of HRV as a predictor of morbidity after tooth extraction. MATERIALS AND METHODS: 30 patients between 16 and 30 years, 15 male, underwent dental extraction of 3rd molar. Monitoring of HRV with time series of RR intervals in 1000, before proceeding with appliance POLAR S810, analyzing variables in the time (SDNN, RMSSD, SD1, SD2 and SD1/SD2), frequency (LF, HF was conducted LF / HF) and nonlinear (Hurst Exponent-HE-LE Lyapunov exponent, DFA and its components alpha1, alpha2 and alfa1/alfa2, using the "software" HRV analysis and DFA. RESULTS: According to a scale of points from the sum of morbid events after extraction (pain, swelling, inflammation, wound healing and psychic), defined a Study Group (12-19 points) and control (0 to 11 points). By analyzing the unpaired t test, considering P ≤ 0.05 value for two-tailed sample, among the studied variables: significant statistical value was found in the medium to Lyapunov exponent (0.999 and 0.885 for the study group and control value p = 0, 0014), SDNN (54.375 and 35.00 for the study and control p-value = 0.0007), RMSSD (46,375 to study and control 37.90 and p-value = 0.0008), SD1 (20,593 to study and 11.73 control and p-value = 0.0007), SD2 (45.468 for study and control 33.20 and p-value = 0.0057) and SD1/SD2 (2,093 and 1,555 for the study and control p-value = 0.0135), the values lower in the study group indicate reduced homeostasis and more linear behavior. The ROC curve analysis showed good sensitivity and specificity for LE, and full DFA ALFA1, with values for the area under the curve of 0.814, 0.656 and 0.662, respectively variables. CONCLUSION: The study of HRV in the time, frequency and nonlinear, for patients with dental extractions, can be used by professional dentists and probably in other areas of health, as a prognostic marker of postoperative clinical complications of Overall, apart from being a simple and easily reproducible.